PENGARUH KEAKTIFAN BERORGANISASI TERHADAP KARAKTER PEDULI SOSIAL MAHASISWA BEM FKIP 2020/2021 UNIVERSITAS RIAU - Lestari, Nuri; Eddison, Ahmad; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by the activeness of the organization and the social care character of BEM FKIP 2020/2021 students at the University of Riau. The formulation of the problem in this study is how the influence of organizational activity on the social care character of BEM FKIP 2020/2021 students at the University of Riau. The purpose of the study was to find out how the influence of organizational activity on the social care character of BEM FKIP 2020/2021 students at the University of Riau. The benefits of this research are theoretical benefits, namely that this research is expected to contribute in the field of education, especially those related to writing scientific papers. Practical benefits, namely as a foothold and reference for further research related to organizational activity and social care character on campus, become material for further study. The population in this study were BEM FKIP students 2017, 2018, and 2019, totaling 68 students. The sample in this study were students of BEM FKIP Riau University, totaling 68 respondents, determined by total sampling technique. Data collection instruments are questionnaires, documentation, and interviews. Data processing with quantitative descriptive analysis using a simple linear regression formula assisted by SPSS version 17 application by stating the hypothesis; there is an influence between organizational activity on the social care character of BEM FKIP students, Riau University. Based on the results of research on the effect of organizational activity on the social care character of BEM FKIP students, Riau University, there is a significant influence between the influence of organizational activity on the social care character of BEM FKIP students, Riau University by 90.7%.Key Words: Influence, Organizational Activity, Social Care Character.